The research of semi-linear hyperbolic system of averaged equations with periodic boundary conditions - Krylovas, Aleksandras; Kriauzienė, Rima (Lietuvos matematikos rinkinys, 2012)
In this paper weakly non-linear hyperbolic system of the first order differential equations with boundary conditions is studied. The averaged system of integro-differential equations along the characteristics is contructed. The aim of this paper is to get the conditions for the existence of classic solution to mentioned averaged problem.
Keywords: asymptotical analysis; averaging; interaction of waves; boundary condition; resonance; the systems of hyperbolic equations